2023
DOI: 10.1039/d2tb01764d
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent peptide recognizes and traps Mycobacterium tuberculosis to inhibit macrophage phagocytosis

Abstract: Tuberculosis (TB) is a major public health concern worldwide, and it is a serious threat to human health for a long period. Macrophage phagocytosis of Mycobacterium tuberculosis (M. tuberculosis) is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Despite the severity of foodborne outbreaks caused by S. Typhi, very little research has been done on the development of electrochemical DNA biosensors specically designed for its detection. Recently, Wang et al 17 have reported that only two studies reported the development of electrochemical DNA biosensors for S. Typhi detection using screen-printed electrodes (SPEs). Both biosensors used a labeled system to detect this serovar.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the severity of foodborne outbreaks caused by S. Typhi, very little research has been done on the development of electrochemical DNA biosensors specically designed for its detection. Recently, Wang et al 17 have reported that only two studies reported the development of electrochemical DNA biosensors for S. Typhi detection using screen-printed electrodes (SPEs). Both biosensors used a labeled system to detect this serovar.…”
Section: Introductionmentioning
confidence: 99%